Decellularized cartilage scaffolds derived from wharton's jelly facilitate cartilage regeneration and inhibit angiogenesis - Fawei Gao; Shilong Su; Jun Qi; Zhigang Li; Chenggong Wang; Da Zhong (Materials Today Bio)
The avascular nature of articular cartilage severely limits its ability to self-repair after injury, which poses a challenge for clinical treatment, and tissue engineering aims to address this issue with scaffold-based strategies. However, the defining characteristics of an optimal scaffold remain controversial. In this study, we prepared two types of decellularized wharton's jelly (dWJ) scaffolds by trypsin combined with repeated freeze-thawing (TFT) and nuclease combined with repeated freeze-thawing (NFT), respectively. The scaffolds were tested with general characterization, decellularization effect, extracellular matrix (ECM) composition and structure retention, mechanical properties, biocompatibility, in vivo and in vitro chondrogenic effects, and in vitro anti-angiogenic effects. The results showed that the TFT-dWJ scaffolds possessed higher pore size, porosity, and swelling rate, but their Young's modulus was lower than that of the NFT-dWJ scaffolds. Both scaffolds were generally similar in terms of degradation rates. In comparison, the native ECM structure and the major components of collagen and glycosaminoglycans were better preserved in NFT-dWJ scaffolds. Importantly, dWJ scaffolds showed favorable biocompatibility and markedly promoted the chondrogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) in vitro, and accelerated cartilage damage repair in vivo. This was particularly evident with NFT-dWJ. Secondly, the dWJ scaffolds exhibited the capability to inhibit localized angiogenesis in human umbilical vein endothelial cells (HUVECs), a property that could be advantageous for preserving avascularity throughout the cartilage regeneration process. This study presents an ECM-derived scaffold fabrication strategy that optimally preserves matrix composition and microstructure, offering a promising solution for cartilage regeneration.